Doctor on Desima : (Sophia University, 1970)
Chapter one: The Portuguese, the Dutch, and the Spanish in Japan; Chapter two: Some Customs and Beliefs in Japan; Chapter three: Matters of Defense; Chapter four: The Teaching and Practice of of Medicine